2018
DOI: 10.1002/cche.10053
|View full text |Cite
|
Sign up to set email alerts
|

Effects of multiple freeze–thaw cycles on the quality of frozen dough

Abstract: Background and objectives:The multiple freeze-thaw treatment of dough during frozen storage has critical effects on the quality of frozen dough. The effects of multiple freeze-thaw cycles on the cooking properties, textural and rheological properties of frozen dough, as well as the mechanism behind this effect were evaluated in this study. Findings: The result showed that the cooking loss rate and water absorption rate were increased by 66.3% and 13.7%, respectively, compared to the control at four freeze-thaw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 30 publications
(56 reference statements)
4
26
0
Order By: Relevance
“…The TPA of steamed bread simulates hewing movements and has been accepted universally (Zhang et al 2018c). The frozen dough was 0.7 cm thick and 3.0 cm in diameter.…”
Section: Texture Profile Analysis (Tpa)mentioning
confidence: 99%
See 2 more Smart Citations
“…The TPA of steamed bread simulates hewing movements and has been accepted universally (Zhang et al 2018c). The frozen dough was 0.7 cm thick and 3.0 cm in diameter.…”
Section: Texture Profile Analysis (Tpa)mentioning
confidence: 99%
“…The springiness of control samples was significantly (P \ 0.05) decreased compared to the fresh samples. These results meant that the taste of dough became worse, especially in noodles and dumplings after the traditional freezing process (Zhang et al 2018c). The cohesiveness was significantly (P \ 0.05) decreased by the traditional freezing process, resulting in inferior dough after it was cooked.…”
Section: Tpa Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, if dough was subjected to multiple freeze–thaw cycles during frozen storage, dough strength was significantly reduced and baked product volume was significantly decreased (Inoue & Bushuk, 1992). Moreover, SEM images revealed that dough structure was damaged (Zhang et al, 2018). Therefore, the molded frozen doughs for all test groups were produced such that the core temperature of the dough reached −20°C; that is, freezing at –30°C for 60 min in a freezing room (Oshikiri Machinery Ltd.).…”
Section: Methodsmentioning
confidence: 99%
“…Experts and scholars at home and abroad have actively explored and studied the problems mentioned above in frozen flour products. Zhang et al (2018) reported the influence of multiple freeze-thaw cycles on the quality of frozen dough. They also used ultrasound-assisted freezing to decrease freezing…”
Section: Introductionmentioning
confidence: 99%